A class of nonlinear variational inequalities involving pseudomonotone operators. (2000) - Verma, Ram U.
Abstract : We present the solvability of a class of nonlinear variational inequalities involving pseudomonotone operators in a locally convex Hausdorff topological vector spaces setting. The obtained result generalizes similar variational inequality problems on monotone operators.